Aspek psikologis dan sosiologis dalam pendidikan: dasar dasar pengembangan kurikulum - Neiza Perdia Putri; Dini Andriani; Gusmaneli (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2024)
Effective curriculum development must consider students' psychological and sociological aspects so that learning runs optimally. The psychological aspect focuses on understanding stages of cognitive development, learning theories, and motivation, as well as student-centered learning approaches. On the other hand, the sociological aspect highlights the importance of social and cultural values, socialization, and social justice and inclusion. The integration of these two aspects can be realized through strategies such as collaborative learning, differentiated learning, character education, and the use of technology. This approach not only increases academic achievement, but also shapes students' social skills and character, so that they are ready to face social challenges in life. Thus, a holistic curriculum can support the creation of a generation that is knowledgeable, has character and is responsive to the social environment.